Dismantling Persistent Deficit Narratives About the Language and Literacy of Culturally and Linguistically Minoritized Children and Youth: Counter-Possibilities - Wang, Su-hua; Lang, Nora; Bunch, George C.; Basch, Samantha; McHugh, Sam R.; Huitzilopochtli, Salvador; Callanan, Maureen (Frontiers in Education, 2021)
Despite decades of efforts, deficit narratives regarding language development and use by children and students from historically marginalized backgrounds remain persistent in the U.S. Examining selective literature, we discuss the ideologies that undergird two deficit narratives: the notion that some children have a “word gap” when compared to their White middle-class peers, and students must develop “academic language” to engage in rigorous content learning. The “word gap” concept came from a study wherein a group of young children in low-income families heard fewer words than those in middle-class families. It assumes that language can only be acquired in one way—vocabulary exchange from one parent to one child—and ignores decades of research on diverse pathways for language development. We highlight an alternative perspective that language development builds on children’s experience with cultural practices and the harm on minoritized children by privileging a specific form of vocabulary acquisition. The second deficit narrative concerns “academic language,” a concept championed by scholars aiming to address educational inequity. The construct runs the risk of undervaluing the potential of students from historically marginalized backgrounds to engage in learning using language that is “informal,” nonconventional, or “non-native like.” It also is sometimes used as a rationale to relegate students to special programs isolated from more rigorous academic discourse, thus ironically removing them from opportunities to develop the academic registers they are deemed to be missing. We explore alternative frameworks that shift the focus from linguistic features of academic talk and texts as prerequisites for academic work to the broad range of linguistic resources that students employ for academic purposes in the classroom. Finally, we turn to a positive approach to youths’ language development and use: translanguaging by multilingual learners and their teachers. Translanguaging demonstrates the power of a resource-oriented perspective that values students’ rich communicative repertoires and actively seeks to disrupt language hierarchies. We argue that this approach, however, must be considered in relation to the broader social context to meet its transformative aims. Together, our analysis suggests counter-possibilities to dismantle deficit-oriented narratives and points to promising directions for research and practices to reduce inequity in education.